Impact of Lupin Inclusion on the Rheological and Qualitative Characteristics, and Sensory Acceptability of Baked Rolls - Tatiana Holkovičová; Zlatica Kohajdová; Michaela Lauková; Lucia Minarovičová; Ladislav Staruch (Polish Journal of Food and Nutrition Sciences)
Lupin represents a high-protein and high-fibre non-traditional raw material that can improve the nutritional value of baked goods. This study investigated the effect of the incorporation of lupin flour on the rheological characteristics of wheat dough as well as qualitative characteristics, sensory acceptability and nutritional value of baked rolls. The rheological properties of blended flours enriched with various weight proportions of lupin flour (5–25%) were analysed via Mixolab. Compared with the control sample (wheat flour), lupin flour increased water absorption from 55.00% to 68.05% and decreased dough stability from 9.32 to 6.86 min. Qualitative assessment of baked rolls revealed a significant reduction in volume (from 252.50 mL to 123.75 mL) and specific volume (from 285.19 mL/100 g to 142.30 mL/100 g) with increasing lupin addition to flour blends. Instrumental color analysis revealed darker, more yellow hue with L * values decreasing from 74.94 to 69.95. Nutritional analysis demonstrated higher protein (19.14g/100 g) and total dietary fibre contents (13.24 g/100 g) in the rolls from the blend enriched with 25% lupin flour. Sensory evaluation indicated that baked goods produced from the flour blends containing up to 15% lupin maintained acceptable sensory qualities, while higher lupin levels adversely affected flavor, porosity, and overall acceptability of the rolls. Correlation analysis showed strong associations between dough stability and starch content ( r =0.941) and the C2 parameter of the Mixolab ( r =0.916). These results suggest that while lupin flour enhances the nutritional profile of baked rolls, optimal incorporation levels (up to 15% in the flour blend) are necessary to maintain product quality and consumer acceptance.